Spine bone mineral density increases in experienced but not novice collegiate female rowers - Lariviere, J. A.; Robinson, T. L.; Snow, C. M. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: There is evidence that rowing exercise targets the spine, but the dose of exercise required to build bone is poorly understood. To further explore this topic, we studied the bone response at the spine in novice and experienced female collegiate rowers over their 6-month competitive season. We hypothesized that, with rowing strokes similar between groups during training, experienced rowers would produce greater force at the spine than novices and thus, gain more bone mineral density (BMD). METHODS: Subjects included 16 experienced rowers (21.2 +/- 1.2 yr) who had been rowing 26 +/- 10 months and 19 novice rowers (19.5 +/- 0.8 yr) who had been rowing three months and 14 controls (19.2 +/- 1.6 yr). BMD was assessed by DXA at baseline and after the 6-month competitive season. During the season, all rowers participated in the same training program and took approximately the same number of strokes per training session (1000-1200 repetitions). On the 2000- and 6000-m rowing ergometer tests experienced rowers had faster times, indicating that their power output, and thus force production, was greater than novices. RESULTS: In ANCOVA, adjusting for body mass index, age, and initial BMD, the experienced rowers demonstrated a 2.5% increase at the spine that was significantly different than that of the novice rowers, but BMD change scores in the rowing groups were not different than controls. CONCLUSION: Because the number of strokes (repetitions) was similar between rowing groups during training, the higher power output in experienced rowers produced higher forces at the spine over the 6-month period that resulted in gains in spine BMD. These results support the theory that force magnitude is a key variable in osteogenesis.